Microfluidic-assisted biomineralization of CRISPR/Cas9 in near-infrared responsive metal-organic frameworks for programmable gene-editing - Xu Xiaoyu; Liu Chang; Wang Shengyi; Mäkilä Ermei; Wang Jiali; Koivisto Oliver; Zhou Junnian; Rosenholm Jessica M; Shu Yilai; Zhang Hongbo (ROYAL SOC CHEMISTRY, 2022)
Ribonucleoprotein (RNP) based CRISPR/Cas9 gene-editing system shows great potential in biomedical applications. However, due to the large size, charged surface and high biological sensitivity of RNP, its efficient delivery with precise control remains highly challenging. Herein, a microfluidic-assisted metal-organic framework (MOF) based biomineralization strategy is designed and utilized for the efficient delivery and remote regulation of CRISPR/Cas9 RNP gene editing. The strategy is realized by biomimetic growing of thermo-responsive EuMOFs onto photothermal template Prussian blue (PB). The RNP is loaded during MOFs crystallization in microfluidic channels. By adjusting different microfluidic parameters, well-defined and comparable RNP encapsulated nanocarrier (PB@RNP-EuMOFs) are obtained with high loading efficiency (60%), remarkable RNP protection and NIR-stimulated release capacity. Upon laser exposure, the nanocarrier induces effective endosomal escape (4 h) and precise gene knockout of green fluorescent protein by 40% over 2 days. Moreover, the gene-editing activity can be programmed by tuning exposure times (42% for three times and 47% for four times), proving more controllable and inducible editing modality compared to control group without laser irradiation. This novel microfluidic-assisted MOFs biomineralization strategy thus offers an attractive route to optimize delivery systems and reduce off-target side effects by NIR-triggered remote control of CRISPR/Cas9 RNP, improving the potential for its highly efficient and precise therapeutic application.